1996
DOI: 10.1097/00005344-199611000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the New Calcium Antagonist Lercanidipine and Its Enantiomers on the Migration and Proliferation of Arterial Myocytes

Abstract: The in vitro effects were investigated of the new dihydropyridine calcium antagonist (CA) lercanidipine and its enantiomers on arterial myocyte (smooth muscle cell; SMC) migration and proliferation as related to L-type calcium channel inhibition. Lercanidipine and its enantiomers inhibited the replication and migration of arterial myocytes in concentration ranging from 10 to 50 microM. The antiproliferative effect of lercanidipine, evaluated as cell number, was dose dependent, with a potency similar to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
3
24
0
5
Order By: Relevance
“…hSMCs were cultured using the SMC Growth Medium 2 Bullet Kit , purchased from BioWhittaker Inc. Mouse primary aortic SMCs (mSMCs) were prepared from aortas of 8-to 12-week-old PPARα +/+ or PPARα -/-mice on Sv/129 or C57BL/6J genetic backgrounds or of p16 +/+ or p16 -/-mice on a C57BL/6J genetic background as described (57) and were studied between the third and twelfth passages. mSMCs were cultured in DMEM supplemented with 10% FCS and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…hSMCs were cultured using the SMC Growth Medium 2 Bullet Kit , purchased from BioWhittaker Inc. Mouse primary aortic SMCs (mSMCs) were prepared from aortas of 8-to 12-week-old PPARα +/+ or PPARα -/-mice on Sv/129 or C57BL/6J genetic backgrounds or of p16 +/+ or p16 -/-mice on a C57BL/6J genetic background as described (57) and were studied between the third and twelfth passages. mSMCs were cultured in DMEM supplemented with 10% FCS and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…One relevant exception may be represented by smooth muscle cells, in which Ca 2+ VOCs are expressed at relatively high densities, and that can actively proliferate in inflammation and hypertrophic growth of blood vessels and other organs; in this case, too, most of the evidence is indirect, based on the effects of VOCs blockers [see e.g. 4,[27][28][29][30]. Expression of L-type channels has been associated with long-term exposure to transforming growth factor β (TGFβ) and ensuing transformation of hepatic stellate cells [31].…”
Section: Voltage Operated Channels (Vocs)mentioning
confidence: 99%
“…88,89 Similarly, experiments with rat aortic VSMCs suggested that in contrast to nifedipine, amlodipine-elicited inhibition of serum-, thrombin-, and basic fibroblast growth factor-triggered VSMC proliferation involved mechanisms independent of CCB properties. 84 In support of this hypothesis, amlodipine has been reported to inhibit thrombin-induced Ca 2ϩ mobilization from thapsigargin-sensitive, internal Ca 2ϩ stores; this effect could not be obtained with isradipine, diltiazem, and verapamil.…”
Section: Effect On Calcium Signalingmentioning
confidence: 99%